PENGARUH KESETARAAN GENDER DI ERA GLOBALISASI TERHADAP KONSEP HARTA BERSAMA DALAM SISTEM KEWARISAN ISLAM - Muhyidin, Muhyidin (Diponegoro Private Law Review, 2018)
Fiqh as part of Islamic law is not impermeable to social change, even the development of fiqh in Islam shows the answers of the fuqaha to the circumstances and conditions of his time. Likewise, in the era of globalization that shows a broad change in the level of human life, the changes which will actually give impact to the thought of fiqh which has been held and used as a guide. This paper will try to see to what extent the concept of gender equality as one of the products of globalization will affect the system of common property in the system of Islamic inheritance. The author sees the change in the concept of gender should affect the concept of common property that has been constructed in legislation. Keywords: Gender Equality, Globalization and Joint Treasure